Formulasi Sediaan Krim Menggunakan Kolagen Tulang Ikan Patin (Pangasius sp.) sebagai Anti Aging - Sudewi Sudewi; Nilsya Febrika Zebua; Shelva Filiana Sari (Journal of Pharmaceutical and Health Research, 2020)
Patin fish (Pangasius sp.) is a fish that has been cultivated by many people because it has a high content of omega 3. People consume patin fish meat as a source of protein, while patin fish bones are only disposed of as waste. Collagen is a protein derivative that has the effect of maintaining skin elasticity. This study aims to determine whether the patin fish bones contain collagen and is there an influence of the use of anti-aging collagen patin fish bone cream on the results of changes in facial skin care. Collagen characterization using infrared spectrophotometry and formulated into cream preparations with concentrations of 1%, 1,5%, 2,5%, 3,5% and evaluation of preparations include homogeneity test, pH measurement, emulsion type determination test, stability test, skin irritation to volunteers and anti-aging effectiveness test. The results showed that patin fish bones contained collagen at wave numbers 3250-3350 cm-1 and 1260-1630 cm-1 which indicated the presence of amine and amide groups. The use of patin fish collagen cream affects the changes in texture, wrinkles, moisture, blemishes and pores become smoother. The best formulation is the formula that contains 3,5% of patin fish bone collagen